Analysis of the electrical regulations applied to the activities of the electrical sector in the construction and maintenance of electrical distribution networks - Santiago Rodríguez, Mauricio Ricardo
This present document presents an analysis of the normativity in force applied for the operatives in at energy distribution networks, referring to the procedures and safety protocols previously defined at the time of performing an operational work. What is sought with this document is to elaborate an analysis of the normativity applied to the subject of industrial safety and electrical risk; allowing us to identify the risks associated at the worker operative carrying out labors in this sector in the city of Cucuta, Norte de Santander.